2013
DOI: 10.1016/s1001-0742(12)60149-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of estrogens and estrogenic activities in water from three rivers in Tianjin, China

Abstract: Studies on estrogenic disrupting compounds (EDCs) occurrence and identification of main responsible compounds in river water discharged into the sea are of significance. In the present research, we screened estrogenic activities of 10 river water samples from 3 main rivers discharged into Bohai Sea in Tianjin using a recombinant two-hybrid yeast assay and chemical analysis by gas chromatography-mass spectrometry. All sample extracts induced significant estrogenic activity, with 17β-estradiol equivalents (EEQ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
(29 reference statements)
2
19
1
Order By: Relevance
“…These river samples were obtained from areas located near agricultural activities. The strong influence of agricultural activities on the occurrence of steroid hormones is also reported by Lee et al (2007) and Rao et al (2013). Moreover, Kolodziej et al (2003) demonstrated that farming waste could contribute to occurrence of steroid hormones in surface water.…”
Section: Steroid Estrogen Concentrations In Surface Water and Sedimensupporting
confidence: 57%
“…These river samples were obtained from areas located near agricultural activities. The strong influence of agricultural activities on the occurrence of steroid hormones is also reported by Lee et al (2007) and Rao et al (2013). Moreover, Kolodziej et al (2003) demonstrated that farming waste could contribute to occurrence of steroid hormones in surface water.…”
Section: Steroid Estrogen Concentrations In Surface Water and Sedimensupporting
confidence: 57%
“…The third river named Beitang River in China E1 ranged from 4.29 to 49.8 ng/L, for E2 from 2.51 to 21.2 ng/L and EE2 was from 1.64 to 24.4 ng/L. In addition, Rao et al (2013) reported that estrogens from three river water samples in Tianjin, China ranged from 0.64 to 50, 1.87 to 11.5 and 1.55 to 24.4 ng/L for E1, E2 and EE2 respectively. Furthermore, Rocha et al (2016) reported an unexpectedly high level of estrogens in Mira River in Portuguese, obtained an annual average estrogen 57 ng/L.…”
Section: Recovery Resultsmentioning
confidence: 99%
“…Yang et al [21] assessed the estrogenic pollution of water samples from various rivers and wastewater treatment plants in Shanghai, China, where the estrogenic activities of river waters range from 2.48 ng/L to 41.9 ng/L. Rao et al [33] determined the estrogenic activities of water samples from 3 rivers in Tianjin, China, and the values ranged from 5.72 ng/L to 59.06 ng/L. Compared with river water in China's urban regions, our data showed that river water from the Xin'an River received relatively less estrogenic pollution caused by human activities.…”
Section: Edcs In Bile Samples Collected From Xin'an River and Farmer mentioning
confidence: 99%